Single-cell RNA sequencing and immune microenvironment analysis reveal PLOD2-driven malignant transformation in cervical cancer - Zhiheng Lin; Fengxin Wang; Renwu Yin; Shengnan Li; Yuquan Bai; Baofang Zhang; Chenlin Sui; Hengjie Cao; Dune Su; Lianwei Xu; Honghong Wang (Frontiers in Immunology)
BackgroundCervical cancer is the fourth most common cancer in women globally, and the main cause of the disease has been found to be ongoing HPV infection. Cervical cancer remains the primary cause of cancer-related death despite major improvements in screening and treatment approaches, especially in low- and middle-income nations. Therefore, it is crucial to investigate the tumor microenvironment in advanced cervical cancer in order to identify possible treatment targets.Materials and methodsIn order to better understand malignant cervical cancer epithelial cells (EPCs), this study used bulk RNA-seq data from UCSC in conjunction with single-cell RNA sequencing data from the ArrayExpress database. After putting quality control procedures into place, cell type identification and clustering analysis using the Seurat software were carried out. To clarify functional pathways, enrichment analysis and differential gene expression were carried out. The CIBERSORT and ESTIMATE R packages were used to evaluate the immune microenvironment characteristics, and univariate and multivariate Cox regression analyses were used to extract prognostic features. Furthermore, assessments of drug sensitivity and functional enrichment were carried out.ResultsEight cell types were identified, with EPCs showing high proliferative and stemness features. Five EPC subpopulations were defined, with C1 NNMT+ CAEPCs driving tumor differentiation. A NNMT CAEPCs Risk Score (NCRS) model was developed, revealing a correlation between elevated NCRS scores and adverse patient outcomes characterized by immune evasion. In vitro experiments validated that the prognostic gene PLOD2 significantly enhances proliferation, migration, and invasion of cervical cancer cells.ConclusionThis investigation delineated eight cell types and five subpopulations of malignant EPCs in cervical cancer, establishing the C1 NNMT+ CAEPCs as a crucial therapeutic target. The NCRS model demonstrated its prognostic capability, indicating that higher scores are associated with poorer clinical outcomes. The validation of PLOD2 as a prognostic gene highlights its therapeutic potential, underscoring the critical need for integrating immunotherapy and targeted treatment strategies to enhance diagnostic and therapeutic approaches in cervical cancer.